A Case Of Neuroendocrine Carcinoma Expressing Myeloid Markers By Flow Cytometry And Review Of the Literature. Issue 2 (5th July 2016) - Harrison, Melody K.; Vanderjagt, Timothy J.; Zhang, Qian‐Yun
Abstract : Background: Flow cytometric data is often analyzed in isolation, without the benefit of clinical and morphologic context, and the findings must be interpreted with caution when unexpected results are obtained. Methods: A bone marrow aspirate from a 69‐year‐old female with incidentally discovered pancytopenia was initially analyzed by flow cytometry alone. The results were subsequently correlated with clinical, morphologic, immunohistochemical, and cytogenetic findings. Results: Morphology and immunohistochemistry confirmed metastatic small cell carcinoma; by flow cytometric analysis, the neoplastic cells were positive for CD56 and showed unexpected expression of CD13 and CD117, raising the possibility of a myeloid neoplasm. Conclusions: Flow cytometric markers are not entirely sensitive or specific, and aberrant expression or lack of expression of certain markers can complicate interpretation, particularly when this is done in isolation (i.e., in reference laboratories). Whenever possible, clinical and morphologic correlation is strongly recommended. © 2016 International Clinical Cytometry Society